Kajian Program Pembinaan Pedagang Makanan Jajanan Anak Sekolah Keliling di Wilayah Kerja Puskesmas Godean I Terhadap Higiene Sanitasi dan Cemaran Escherichia coli - Nurul Hasanah; Iswanto Iswanto; Wiranto Wiranto (Fakultas Kedokteran Universitas Gadjah Mada, 2020)
Purpose: To find out the implementation and influence of the Puskesmas Godean I training program on sanitation and Escherichia coli contamination on school-based street food vendors in the Godean sub-district.Method: The type of research conducted is observational research. The study design was cross-sectional. The research sample was school-based street food vendors in the Puskesmas Godean I working area. The sampling technique used was total sampling.Result: This study found that there were significant differences between vendors who took part in the training and those who did not take part in the training in terms of personal hygiene (p = 0.002; p <0.05) and sanitation of food equipment (p = 0.028; p <0.05). While there was no significant difference in terms of food serving sanitation (p = 0.285; p <0.05), sanitation facilities of vendors (p = 0.154; p <0.05), and Escherichia coli contamination (p = 0, 126 ; p <0.05).Conclusion: The training program on the hygiene of sanitation and Escherichia coli contamination for school-based food vendors in the work area of Puskesmas Godean I has been implemented, even though it has not been effective. There is an influence of training programs for school-based food vendors on personal hygiene and food equipment sanitation.